2022
DOI: 10.1186/s12879-022-07668-w
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic parameters of vancomycin for predicting clinical outcome of enterococcal bacteremia

Abstract: Purpose To find pharmacokinetic/pharmacodynamic parameters of vancomycin associated with the optimal outcome of severe infection due to Enterococcus species. Methods We retrospectively reviewed enterococcal bacteremia cases treated with vancomycin from January 2015 to December 2020. The primary outcome was 30-day mortality. We calculated cutoff values of the ratio of vancomycin area under the concentration–time curve over 24 h to the minimum inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
1
11
2
Order By: Relevance
“…Patients in Group A (albumin <2.0 mg/dl and MIC ≥1 μg/ml) had a significantly shorter survival time than those in Group B (the rest). From previous studies (9)(10)(11), AUC 24 /MIC, age, and trough VCM levels, have been identified as factors affecting 30-day mortality, but to our knowledge, there have been no previous reports evaluating the impact of nutritional indicators such as albumin on 30-day mortality. These results suggest that in patients with E. faecium bacteremia with MIC ≥1 μg/ml and hypoalbuminemia (albumin <2.0 mg/dl), it is important to provide more focused support, including TDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in Group A (albumin <2.0 mg/dl and MIC ≥1 μg/ml) had a significantly shorter survival time than those in Group B (the rest). From previous studies (9)(10)(11), AUC 24 /MIC, age, and trough VCM levels, have been identified as factors affecting 30-day mortality, but to our knowledge, there have been no previous reports evaluating the impact of nutritional indicators such as albumin on 30-day mortality. These results suggest that in patients with E. faecium bacteremia with MIC ≥1 μg/ml and hypoalbuminemia (albumin <2.0 mg/dl), it is important to provide more focused support, including TDM.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated the effect of MIC on the therapeutic effectiveness and the AUC 24-48 h /MIC on the second day of treatment based on AUC 24-48 h calculated using PAT. Previous studies (9)(10)(11) have included two strains of Enterococcus, E. faecium and E. faecalis, as the target infecting organisms, and there are few reports limited to E. faecium. Therefore, limiting this study to patients with E. faecium bacteremia yields novel findings.…”
Section: Discussionmentioning
confidence: 99%
“…and coagulase-negative Staphylococcus (CoNS) 3 despite the high prevalence of serious infections with these bacteria. 6 Previous studies of vancomycin treatment outcomes for Enterococcus indicated that all-cause mortality rates were lower when the AUC 24 /MIC was in the range 389-504, [7][8][9][10] whereas outcomes for C trough were inconclusive. [7][8][9][10][11][12] One study of CoNS infections indicated that AUC/MIC was a suitable index for bacterial killing effect and emergence of vancomycin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…6 Previous studies of vancomycin treatment outcomes for Enterococcus indicated that all-cause mortality rates were lower when the AUC 24 /MIC was in the range 389-504, [7][8][9][10] whereas outcomes for C trough were inconclusive. [7][8][9][10][11][12] One study of CoNS infections indicated that AUC/MIC was a suitable index for bacterial killing effect and emergence of vancomycin resistance. 13 As these studies were run either retrospectively [7][8][9][10][11][12] or in an animal model, 13 their results may not be directly applicable to patient care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation